2007
DOI: 10.4103/0971-9261.40837
|View full text |Cite
|
Sign up to set email alerts
|

Splenic injuries in children: The challenges of non operative management in a developing country

Abstract: Aim: This is to report the challenges and experience gained with non operative management of splenic injuries in a developing country where sophisticated imaging facilities are either not available or exorbitantly expensive. Materials and Methods: All patients who presented with splenic injury at the University of Benin Teaching Hospital between January, 2000 and December, 2006 were assessed and those who met the criteria were recruited for non operative management. Diagnosis of splenic injury was made by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 25 publications
5
10
2
Order By: Relevance
“…Splenic injuries are commonly associated with other injuries and these may complicate the management and affect the outcome [17]. The pattern of complications in the present study is similar to what was reported by others [13,17].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Splenic injuries are commonly associated with other injuries and these may complicate the management and affect the outcome [17]. The pattern of complications in the present study is similar to what was reported by others [13,17].…”
Section: Discussionsupporting
confidence: 88%
“…The high incidence of blunt splenic injuries in this study can be explained by the fact that those patients who had blunt splenic injuries were mostly involved in road traffic crash, a common feature of increased motorization in this environment. Road traffic accidents have been reported to be the commonest cause of blunt splenic injuries in most studies as supported by the present study [ 7 , 11 , 13 , 15 , 17 ]. In contrast to our findings, one study reported fall from height as the most common cause of splenic injuries [ 21 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations